Theory of phantomization of radio images of SAR: basic information and justification of the sizes of the phantom area - Volodymyr Pavlikov; Pavlo Pozdniakov; Eduard Tserne; Denys Kolesnikov; Maksym Peretiatko; Pavlo Malashta (Авіаційно-космічна техніка та технологія)
The article's subject of study is the creation of the foundations of the theory of the formation of false elements in the images of aerospace radio vision systems by injecting informational signs of objects absent on the underlying surface. The goal is to substantiate the dimensions of the subsurface areas on which it is possible to simulate objects with different methods of viewing the exploring area from the aerospace radar carrier. Task: to develop the geometry of the problem, which will reflect the interaction between the radar with the synthesis of the Synthetic-aperture radar (SAR) and the radar of phantomization (FR); to develop a general structural diagram of the FR; determine the main parameters, taking into account which will allow planning an "interaction" session between the SAR and the FR; to determine the sizes of the underlying surface areas, where it is possible to provide phantomization of radio images formed by SAR with different methods of examination. The methods used are mathematical and functional analysis, navigation, and remote sensing. The following results were obtained. The geometry of the problem of the interaction between the SAR and the FR was defined; it allowed us to calculate the interaction time between the systems and to establish the law of change of the distance between them at any placement of the SAR in orbit. The influence of the interposition of the considered systems on the expected shape of the SAR sounding signal and the size of the area on which the problem of radio image phantomization arises has been investigated. Examples of calculations of the specified parameters for various types of exploring of the earth's surface by radar from an aerospace carrier are given. Conclusions. The article summarizes and develops the theory of phantom radio images constructed using SAR. The obtained results establishing the dependence between the phantomization geometry and such parameters as the potential and actual time of interaction between the systems, the envelope of the bundle of received radio pulses, and the number of separation bands by range are important for further research in this direction, which at the moment it is advisable to focus on solving the optimization problem phantomization of separate blocks of the radar and determining the conditions for planning the processes of injecting objects into the transmitter signal and into the radio image formed by the SAR.